The Differences Between Arabic Language Teaching for Single Rooted Foreign Speakers and Multiple Rooted Foreign Speakers: Case study: The teaching of Arabic Language in Assalam Islamic Boarding School, Indonesia and An-Nile Center of Arabic Language Study for Foreigner, Cairo - Alfiyatul Azizah (Ittishal Educational Research Journal, 2020)
The Arabic language teaching has been developed rapidly through this modern era as a result of the world wide acceptance to study this language. Language enthusiasts as well as the scholars have noticed some development of Arabic language on several ways as well as its advancement according to the linguistic and geographic condition of learners. This study aims to understand some differences of Arabic language teaching for students who speak in single rooted language and students who speak in multiple rooted language. The single rooted language one took a sample from Assalam Islamic Boarding School where all of the student came from single rooted language, Malay language. While another one took a sample from An-Nile Center of Arabic Language Study for Foreigner, Cairo where the students came from several roots of languages, such as Malay, European, Russian, Turkish, African, and so on. In addition, this study aims to understand some difficulties and challenges the students and teachers face, and compare the percentage results of 4 language development skills between the two groups. The result of this study, based on those two institutions’ Arabic teaching methods, it is concluded that the comparison result of 4 language skills shows that the Arabic teaching method for Multiple Rooted Foreign Speakers (Taken from An-Nile Arabic Language Center) is better than Arabic teaching for the single rooted language speakers, especially on the speaking skill. In another side, we found that one of reasons why Arabic teaching method for foreigners from single rooted language speakers is weaker— is due to the tendency of language teachers to perform translation for Arabic words into their own particular language and the less of creative media invention uses which allow them to explain Arabic words with Arabic language.